Comparative Analysis of Outcome between Laparoscopic versus transabdominal Open Surgical Repair for Vesicovaginal Fistula (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Objectives: Vesicovaginal fistulas (VVF) have detrimental psychosomatic effects on women. Many publications exist on various approaches to VVF repair. Most of the surgeons are trained in open repair of VVF. Laparoscopic VVF repair is gaining popularity. The purpose of this study is to report our experience in the repair of vesicovaginal fistulas (VVF) by open and laparoscopic techniques and compare outcomes.Material and methods: A retrospective study was conducted with the data of the patients who underwent VVF repair from 2017 to 2022. Out of the 60 VVF patients, 27 were managed laparoscopically (group 1) and 33 by open repair (group 2). Data on the etiology, size, number, location, mean operative time, need for blood transfusion, and postoperative complications were analyzed.Results: The mean operative time (hours) in the laparoscopic group (group 1) was (5.01 ±1.06), and in the open group (group 2), it was (3.09 ± 1.03; p